FOR USE FOAM FILLING IRON REMOVAL WATER - and (Municipal economy of cities. Series: «Economy science», 2013)
Definitely promising uses of plastics in water management. Results of Hydraulic Research filtering process due to foam filling, results filtering and cleaning processes.